The rise of the yen vis–vis the ("synthetic") euro: is it supported by economic fundamentals? - Bernd Schnatz; Chiara Osbat; Rasmus Rüffer (European Central Bank (ECB), 2003)
This paper examines the long-run determinants of the euro-yen exchange rate. Using cointegration analysis, we find a consistent and significant relationship between the real exchange rate and relative productivity, the net foreign asset position, relative government spending and terms of trade shocks, as well as a fairly rapid mean reversion of the exchange rate to its equilibrium. The "equilibrium" rate tracks the trends in the actual exchange rate quite well, accounting for a large part of the yen appreciation from the mid-1970s to 2001. Our findings suggest that the euro appreciation against the yen in 2001 represented an equilibrium correction of its previous depreciation. Moreover, the width of the error bands highlights the difficulties arising when attempting to determine the precise equilibrium value of a currency.
Keywords: F31; C32; 330